"Touch Me If You Can!": Individual Differences in Disease Avoidance and Social Touch. (October 2021) - Thiebaut, Gaëtan; Méot, Alain; Witt, Arnaud; Prokop, Pavol; Bonin, Patrick
The threat of diseases varies considerably among individuals, and it has been found to be linked to various proactive or reactive behaviors. In the present studies, we investigated the impact of individual differences in the perceived vulnerability to disease (PVD) on social touch before (Study 1) or during the coronavirus disease 2019 (COVID-19) pandemic (Study 2). We also investigated the influence of personality traits in the covariation between these two dimensions. We found that people who are the most disease-avoidant are also the most reluctant to touching or being touched by others (and this relationship holds when personality traits are taken into account). Interestingly, the association between PVD and social touch increased during the COVID-19 pandemic compared with a few months before. By showing that the fear of contamination has an association with social touch, the findings provide further evidence for the behavioral immune system (Schaller and Park, 2011 ), a psychological system acting as a first line of defense against pathogens.